Sonochemical synthesis of two nano-sized nickel(II) coordination polymers derived from flexible bis(benzimidazole) and isophthalic acid ligands. (1st March 2019) - Li, Jun-Xuan; Liu, Dong; Qin, Zhan-Bin; Dong, Gui-Ying
Graphical abstract: Two nano-sized Ni(II) coordination polymers (CPs) were synthesized under hydrothermal and Sonochemical condition, 1 exhibits a 3D architecture withCdSO4 topology, while2 displays 2D network withhcb layery. Nano-sized1 displays higher photocatalytic activities than nano-sized2 . Abstract: Two new Ni(II) coordination polymers (CPs), [Ni(L1)(IPA)] n (1 ) and [Ni(L2)(IPA)·H2 O] n (2 ) (L1 = 1, 6-bis(benzimidazol-1-yl)hexane, L2 = 1, 6-bis(5, 6-dimethylbenzimidazol-1-yl)hexane, H2 IPA = isophthalic acid) were synthesized by hydrothermal and sonochemical process. X-ray crystal structure analysis revealed that1 possesses a 4-connected 3D architecture with a 6 5 . 8CdSO4 topology, while2 exhibits a 2D layer, which can be classified as a honeycomb 6 3 -hcb network. The results indicate that Ni(II) mixed CPs structurally modulated by the flexible bis(benzimidazole)-involved co-ligands. The role of ultrasound irradiation power, reaction time and reaction temperature on the size and morphology of the nano-sized1 and2 were investigated in detail. Further, fluorescence and photocatalytic activities of nano-sized CPs for degradation of methylene blue (MB) are presented.